Phenazopyridine abuse presenting with acute kidney injury, hemolytic anaemia and jaundice - Jaya Prakash Nath Ambinathan; Mohamed Elbokyl; Rory McQuillan (Archives of Clinical Nephrology - Peertechz Publications, 2017)
Phenazopyridine, an azo dye, is commonly used to relieve dysuria caused by bladder irritation or infection. We report the case of a 64-year-old lady who presented with unexplained sub-acute onset hemolytic anaemia followed by acute kidney injury (AKI) and jaundice. This created a diagnostic dilemma until concealed phenazopyridine abuse was discovered. Discontinuation of Phenazopyridine improved renal function and hemoglobin level to baseline without any other intervention. Prompt urinalysis proved  crucial in solving the diagnostic challenge. We also present a review of literature highlighting the association of this commonly used medication with renal tubular dysfunction, interstitial nephritis and hemolytic anemia.